Penatalaksanaan Pasien Petani Lansia Dengan Low Back Pain Akibat Kecelakaan Lalu-Lintas Melalui Pendekatan Kedokteran Keluarga Di Wilayah Kerja Puskesmas Natar - Pandiangan, Franklin; Larasati, TA (CV. Jasa Sukses Abadi, 2025)
Low Back Pain (LBP) is one of the most common musculoskeletal disorders encountered in primary healthcare settings. The etiology of LBP is diverse but generally associated with poor posture, heavy or repetitive physical activity, degenerative processes, and psychosocial factors. In Indonesia, the prevalence of LBP is estimated to range from 7.6% to 37% of the general population, with a high proportion linked to physically demanding occupations. Diagnosis of LBP involves a comprehensive history-taking, systematic physical examination, and consideration of supporting investigations if red flags such as fractures, infections, or malignancies are suspected. Identifying the pain source, duration, characteristics, and distribution is crucial in establishing the diagnosis and determining the underlying cause. In clinical practice, a holistic and evidence-based approach by primary care or family physicians is highly recommended. This should include the assessment of internal risk factors such as advanced age and degenerative disease, as well as external factors like a history of strenuous work and physical inactivity. The case of Mr. S, a 73-year-old male, illustrates chronic LBP with worsening symptoms over the past month. The pain radiated to the right buttock and lower limb, leading to functional impairment and limitations in daily activities. A thorough evaluation using the biopsychosocial model and multidisciplinary management—including pharmacotherapy, patient and family education, targeted physical exercises, and lifestyle modifications—resulted in significant symptom improvement and increased patient awareness of the condition.